2004
DOI: 10.7205/milmed.169.3.184
|View full text |Cite
|
Sign up to set email alerts
|

The “Golden Hour” for Heatstroke Treatment

Abstract: Exertional heatstroke is a life-threatening event. It occurs mainly among the young healthy populations of athletes and soldiers. The severity of exertional heatstroke is directly correlated to the area under the temperature duration curve. Therefore, rapid cooling in the field has an enormous effect on prognosis. Four cases of exertional heatstroke are presented which differ in their outcome. We argue that there is a "window time period" within which simple and effective cooling techniques can determine progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 10 publications
1
71
0
Order By: Relevance
“…3,12,13,16 We demonstrated that the CS treatment produced faster cooling rates than no treatment; however, the rate of cooling was slower than that produced by currently recommended techniques. 3 We analyzed temperature responses to the treatment protocols using both T re throughout treatment and overall cooling rates.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…3,12,13,16 We demonstrated that the CS treatment produced faster cooling rates than no treatment; however, the rate of cooling was slower than that produced by currently recommended techniques. 3 We analyzed temperature responses to the treatment protocols using both T re throughout treatment and overall cooling rates.…”
Section: Discussionmentioning
confidence: 84%
“…13 The authors 13 attributed this difference to insufficient coverage of the first patient with water. Heled et al 12 doused patients with cold water and implemented intravenous infusion. This method demonstrated a cooling rate of only 0.058C/min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Golden-hour subsumes time to reach definitive-care, thereby including communication/accessibility/reporting time, doctor-patient interaction time and stabilization-time allowing critical clinical interventions. Significant associations with deterioration of patient's condition have been found with each incremental minute of patient arrival to definitive-care [6][7][8][9]. It is important to note that doctor-patient interaction time and stabilization-time may be as long as 27.55 minutes, which may nudge into the golden-hour [10].…”
Section: Public Health and Epidemiologymentioning
confidence: 99%
“…Sometimes, visit come at the cost of leaving the medical facility without a doctor. In any resource limited scenario, most patients who deserve time, access definitive-care beyond the golden-hour [7,8,25,26].…”
Section: Public Health and Epidemiologymentioning
confidence: 99%